2010
DOI: 10.1177/0267659110375645
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of Dideco’s paediatric cardiopulmonary circuit for neonates weighing less than five kilograms

Abstract: The neonate cardiopulmonary bypass (CPB) circuit, including a KIDS D100 oxygenator (The Sorin Group, Mirandola, Italy) and a D130 arterial filter (The Sorin Group), was evaluated in vitro with respect to the removal of free micro gas bubbles. No gas bubbles > 40µm were measured after the arterial filter D130 upon manual introduction of 10 ml of air into the venous line or during the use of vacuum-assisted venous drainage (VAVD). The D130 arterial filter removed 88 % of gas bubbles < 40 µm during manual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Such findings support the present results, showing platelet transfusions on day 0 to be related to the CPB priming volume. A larger prime was related to additional PRBC transfusions on day 0, and this is consistent with previous reports showing that even small reductions in the priming volume may significantly decrease the number of PRBC transfusions in neonates (23). Ultrafiltration, conventional or modified, is routinely used in pediatric patients to reverse hemodilution and has been previously shown to reduce transfusions (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…Such findings support the present results, showing platelet transfusions on day 0 to be related to the CPB priming volume. A larger prime was related to additional PRBC transfusions on day 0, and this is consistent with previous reports showing that even small reductions in the priming volume may significantly decrease the number of PRBC transfusions in neonates (23). Ultrafiltration, conventional or modified, is routinely used in pediatric patients to reverse hemodilution and has been previously shown to reduce transfusions (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…1,2 A study of the D100 showed that it required 37% less prime volume, which resulted in significantly less blood transfusion, ventilation time, and postoperative bleeding when compared with its larger predecessor. 3 An impressive feature of these new oxygenators is that they are able to adequately oxygenate blood at high flow rates (up to 2 L/min) despite having relatively low surface areas. This translates into being able to use these oxygenators on patients as large as 15 kg.…”
Section: Neonatal/pediatric Oxygenatorsmentioning
confidence: 99%
“…1,2 A study of the D100 showed that it required 37% less prime volume, which resulted in significantly less blood transfusion, ventilation time, and postoperative bleeding when compared with its larger predecessor. 3…”
Section: Neonatal/pediatric Oxygenatorsmentioning
confidence: 99%
“…This is the result of the increased commercial availability of sophisticated multichannel emboli detection devices (29,30). Recent in vitro studies in pediatric models of current CPB circuits have demonstrated increased transmission of emboli through the CPB circuit associated with VAVD and that although the number of emboli was attenuated by an arterial filter, they were associated with both reservoir level and higher vacuum (-40 mmHg) (31,32). Studies from the laboratory at Penn State Hershey Children's Hospital similarly show emboli distal to the arterial filter after entrained venous air are exacerbated with higher levels of VAVD and attenuated by the arterial filter.…”
Section: Emboli and Cardiopulmonary Bypassmentioning
confidence: 99%